2012
DOI: 10.30638/eemj.2012.042
|View full text |Cite
|
Sign up to set email alerts
|

Eutrophication Modelling of Golesti Reservoir in Romania

Abstract: Global existence of a large percentage of lakes with eutrophication problems (54% in Romania) demands a predictive tool for the quality of these ecosystems. In this context, this paper proposes an eutrophication model that describes the thermal and biochemical behaviour of an eutrophic reservoir. This model was used to study an artificial lake (Goleşti reservoir) located in Romania. The conceptual model concerns a lake, which is considered as a closed aquatic system, and analyze a simply food web (nutrients, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Dumitran et al, in 2010, forecasted the eutrophication phenomenon observed in Rosu Lake while taking the ecosystem's dynamics into account [71]. Four state variables were considered in the model: TP, TN, zooplankton biomass, and phytoplankton biomass.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dumitran et al, in 2010, forecasted the eutrophication phenomenon observed in Rosu Lake while taking the ecosystem's dynamics into account [71]. Four state variables were considered in the model: TP, TN, zooplankton biomass, and phytoplankton biomass.…”
Section: Resultsmentioning
confidence: 99%
“…The results and experimental data agreed quite well, with the rootmean-square error RMSE values being as follows: 0.33 for TP, 1.47 for Chl a, and 1.98 for TN. Also, the behavior of the eutrophic reservoir Goles , ti was described by Dumitran et al (2012), using a biochemical model coupled with a thermal one [72]. The following data were used to calibrate and validate the model over the period 2008-2009: average water temperature from 2 to 23 • C, DO values from 6.91 to 13.3 mg/L, TN values from 0.2 to 1.18 mg/L, TP values from 0.044 to 1.43 mg/L, and Chl a values from 1.78 to 5.3 mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed ecological model is divided into a hydrodynamic/thermal [4] and a biochemical model [2]. Since the biochemical model needs large number of simulations, a separation between physical and biochemical model was preferred.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental objective for surface water bodies is considered to be achieved when the water bodies attain high ecological status or good ecological potential. The quality of the main lakes and reservoirs in Romania reveals that only 7.85 % from lakes have a good ecological status and 50% from reservoirs have a good ecological potential [2]. Many aquatic ecosystems have become more eutrophic in recent years.…”
Section: Reservoir Managementmentioning
confidence: 99%
See 1 more Smart Citation